'All Are Instructive If Read in a Right Spirit': Reading, Religion, and Instruction in a Victorian Reading Diary. (3rd April 2017) - Weiss, Lauren J.
ABSTRACT: This paper conducts a study of reading choices and practices through the reading diary of a middle-class reader in mid–nineteenth-century Glasgow within the context of her sociocultural, intellectual, and religious milieu. Anne Galloway (1802–1889) wrote her reading diary between 1850 and 1856, wherein she recorded one hundred eighty-four books and three periodicals. This study combines an investigation in the availability of books and their circulation with a focus on Stirling's Library, a subscription library founded by Walter Stirling in 1791, from which Anne obtained her books. Anne's borrowing record is reconstructed using the library catalogues. These are used to assess the different classifications of the books she read and their respective numbers to determine the pattern of Anne's borrowing and reading practices. This investigation offers new insights into Glasgow's book culture through the reconstructed history of a 'lesser-known' Evangelical, nonprofessional, married woman reader in the mid-nineteenth century, demographics of which are currently all underrepresented in individual case studies in the history of reading.